ANALYSIS OF STRUCTURAL PLASTICITY IN THE HONEY BEE BRAIN USING THE CAVALIERI ESTIMATOR OF VOLUME AND THE DISECTOR METHOD - Brown, Sheena M; Napper, Ruth MA; Mercerl, Alison R (Image Analysis and Stereology, 2011)
The antennal lobe of the worker honey bee has been used as a model system to address the origins of structural plasticity in the central nervous system. A combination of light and electron microscopy was used to determine total synapse number within an easily identifiable sub-unit of the antennal lobe neuropil, the T4-2(1) glomerulus. The Cavalieri method was applied at the light microscope level to determine a reference volume (Vref) of this glomerulus. Using transmission electron microscopy, the physical disector was used to determine synaptic density (Nv) within the T4-2(1) glomerulus. An estimate of the total synapse number N(syn) was determined by; N(syn) = V(ref) Nv. Newly emerged, 4-day old,10-day old and forager-aged bees were analysed. Results showed that despite a significant increase in T4-2(1) volume with age, the total number of synapses in this glomerulus did not show a corresponding increase. Disturbingly, it is possible that huge variances within age groups, due to one or two outlying data points, could be masking the true trend of synapse number. This variance, the heterogeneous distribution of synapses within this glomerulus and the problems associated with reproducibility of synapse counts are discussed.